Project Management: A Bibliometric Analysis of Publication Patterns and Research Frontiers - Loso Judijanto; Rini Fitrianingrum (West Science Business and Management, 2026)
This study aims to map the intellectual structure, publication patterns, and emerging research frontiers in project management through a comprehensive bibliometric analysis. Data were collected from the Scopus database and analyzed using VOSviewer to examine co-authorship networks, keyword co-occurrence, and thematic evolution. The results reveal that project management research is anchored by core themes such as decision making, information management, and risk assessment, which form a well-established knowledge base. At the same time, the field is experiencing significant transformation driven by the integration of emerging technologies, particularly artificial intelligence and machine learning, as well as a growing emphasis on sustainability and climate-related issues. The analysis also identifies a distinct yet connected research stream in healthcare and clinical management, highlighting the interdisciplinary application of project management principles. Furthermore, overlay and density visualizations indicate a temporal shift toward more technology-oriented and sustainability-focused topics, reflecting the evolving priorities of both academia and practice. This study contributes to the literature by providing a systematic overview of the development and current trends in project management research, offering insights into future research directions and potential areas for cross-disciplinary integration.